Silencing GFAP isoforms in astrocytoma cells disturbs laminin‐dependent motility and cell adhesion. Issue 7 (2nd April 2014) - Moeton, Martina; Kanski, Regina; Stassen, Oscar M. J. A.; Sluijs, Jacqueline A.; Geerts, Dirk; van Tijn, Paula; Wiche, Gerhard; van Strien, Miriam E.; Hol, Elly M.
ABSTRACT: Glial fibrillary acidic protein (GFAP) is an intermediate filament protein expressed in astrocytes and neural stem cells. The GFAP gene is alternatively spliced, and expression of GFAP is highly regulated during development, on brain damage, and in neurodegenerative diseases. GFAPα is the canonical splice variant and is expressed in all GFAP‐positive cells. In the human brain, the alternatively spliced transcript GFAPδ marks specialized astrocyte populations, such as subpial astrocytes and the neurogenic astrocytes in the human subventricular zone. We here show that shifting the GFAP isoform ratio in favor of GFAPδ in astrocytoma cells, by selectively silencing the canonical isoform GFAPα with short hairpin RNAs, induced a change in integrins, a decrease in plectin, and an increase in expression of the extracellular matrix component laminin. Together, this did not affect cell proliferation but resulted in a significantly decreased motility of astrocytoma cells. In contrast, a down‐regulation of all GFAP isoforms led to less cell spreading, increased integrin expression, and a > 100‐fold difference in the adhesion of astrocytoma cells to laminin. In summary, isoform‐specific silencing of GFAP revealed distinct roles of a specialized GFAP network in regulating the interaction of astrocytoma cells with the extracellular matrix through laminin.—Moeton, M., Kanski, R., Stassen, O. M. J. A., Sluijs, J. A., Geerts, D., van Tijn, P., Wiche, G., van Strien, M. E., Hol, E. M. Silencing GFAP isoforms in astrocytoma cells disturbs laminin dependent motility and cell adhesion. FASEB J . 28, 2942–2954 (2014). www.fasebj.org